Investigation on children's handwashing behaviour and contamination levels in rural Cambodia - Gaku Manago; Kongkea Phan (Journal of Water, Sanitation and Hygiene for Development, 2023)
The present study aimed to investigate children's handwashing behaviour, contamination levels and qualities of water sources used for handwashing in rural Cambodia. A field survey was conducted by simple random sampling in Kandal Leu village of Kandal Province in 2014. Only 23 children were interviewed with the informed consent of their guardians, limiting our data analysis as descriptive. Concurrently, an adenosine triphosphate test kit was used to assess their hands' contamination levels. Their water sources for handwashing were also tested for Escherichia coli and coliform. As a result, approximately 27% of children in the study areas were found not to wash their hands and 17.2% of children washed their hands more than four times a day before and after eating, after touching dirt and after toileting. Approximately 74% of the dirt could be removed from hands by washing with water. Concurrently, approximately 96% of water from traditional rainwater jars (Pieng) used for handwashing was contaminated with coliform, while 65% was contaminated with E. coli. Cambodian children in our study area used polluted rainwater for handwashing in the rainy season. This study suggests that appropriate handwashing requires safe water and educational programs on environmental and personal hygiene for parents and children. HIGHLIGHTS 27% of children under the age of 15 years in the study area were found not to wash their hands.; 17.2% of children under the age of 15 years washed their hands more than four times a day in the study area.; In the rainy season, children under the age of 15 years washed their hands using rainwater.; Rainwater used for washing hands was polluted by coliform and E. coli.; 74% of the dirt could be removed from hands by washing with water.;